Maquiavel e a Literatura Pop Management: o mundo das incertezas e o convite às fantasias organizacionais - Luis Fernando Tosta Barbato; Mateus Henriques Patrício (Ciências Sociais Unisinos)
This article aims at bringing a comparative study of the works The Prince, of Niccolo Machiavelli, and The Servant, of James C. Hunter, and understand how the two books work the issue of leadership. From the analysis of the two works, we intend to show how the laboring subject occupies a central place in discussions of modern society, and to show that, although the two works in question are apparently so antagonistic in their leadership concepts, there is a series of common objectives and strategies that help us better understand the corporate world. Through the analysis of these two works, we were able to conclude that the leadership exercised by Hunter’s benevolent and servant leader, despite seeming so far from Machiavelli’s cold and rational leader, paradoxically does not avoid using the most appropriate strategies to maintain power and win the loyalty of his employees, which shows that Hunter’s conception of leadership does not fail to rely on elements characteristic of Machiavelli.